Frailty and stroke thrombectomy outcomes—an observational cohort study. (12th February 2022) - Joyce, Nevan; Atkinson, Timothy; Mc Guire, Karen; Wiggam, M Ivan; Gordon, Patricia L; Kerr, Enda L; Patterson, Cathy E; McILmoyle, Jim; Roberts, Gerallt E; Flynn, Peter A; Burns, Paul; Rennie, Ian R; et al.
Abstract: Introduction: Mechanical thrombectomy (MT) can improve outcomes following ischaemic stroke. Patient selection for MT is predominantly based on physiological and imaging parameters. We assessed whether people living with pre-stroke frailty had differing outcomes following MT. Methods: We included consecutive patients undergoing MT at a UK comprehensive stroke centre. We calculated a cumulative deficits frailty index to identify pre-stroke frailty in those patients presenting directly to the centre. Frailty was defined as an index score ≥ 0.24. We assessed univariable and multivariable association between pre-stroke frailty and stroke outcomes. Our primary outcomes were modified Rankin Scale (mRS) and mortality at 90 days. Results: Of 175 patients who underwent MT (2014–2018), we identified frailty in 49 (28%). Frail and non-frail patients had similar rates of thrombolysis administration, successful recanalization and onset to recanalization times. Those with pre-stroke frailty had higher 24 hour National Institutes of Health Stroke Scale (12(IQR: 8–17) versus 3(IQR: 2–13); P  = 0.001); were less likely to be independent (mRS 0–2: 18% versus 61%; P  < 0.001) and more likely to die (47% versus 14%; P  < 0.001) within 90 days. Adjusting for age, baseline NIHSS and thrombolysis, frailty remained a strong, independent predictor of poor clinical outcome at 90 days (Death OR: 3.12 (95% CI: 1.32–7.4); dependency OR: 3.04 (95%CI: 1.10–8.44). Age was no longer a predictor of outcome when adjusted for frailty. Conclusion: Pre-stroke frailty is prevalent in real-world patients eligible for MT and is an important predictor of poor outcomes. Routine assessment of pre-stroke frailty could help decision-making around patient selection for MT.